2018
DOI: 10.1002/cpdd.629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food on the Pharmacokinetics of Ertugliflozin and Its Fixed‐Dose Combinations Ertugliflozin/Sitagliptin and Ertugliflozin/Metformin

Abstract: Ertugliflozin, an inhibitor of sodium‐glucose cotransporter 2, is approved in the United States and European Union for the treatment of type 2 diabetes in adults, both as monotherapy and as part of fixed‐dose combination (FDC) therapies with either sitagliptin or immediate‐release metformin. The effect of a standard, high‐fat breakfast on the pharmacokinetics of the highest strengths of ertugliflozin monotherapy (15 mg), ertugliflozin/sitagliptin FDC (15‐/100‐mg), and ertugliflozin/metformin FDC (7.5‐/1000‐mg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
44
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 19 publications
6
44
0
Order By: Relevance
“…Log‐linear regression analyses suggested that mean area under the plasma concentration‐time profile (AUC) values for patients with renal impairment were ≤70% higher compared with those in subjects with normal renal function, although this increase in exposure is not expected to be clinically meaningful . A 2‐period, single‐dose crossover phase 1 study demonstrated that there is no effect of food on the pharmacokinetics of ertugliflozin in healthy volunteers and that ertugliflozin 15 mg can be administered without regard to meal consumption . The potential for ertugliflozin to be a victim or perpetrator of clinically meaningful drug interactions is low: a number of phase 1 studies have shown that there is no clinically relevant drug‐drug interaction between ertugliflozin and metformin, sitagliptin, glimepiride, simvastatin, or rifampin…”
mentioning
confidence: 99%
“…Log‐linear regression analyses suggested that mean area under the plasma concentration‐time profile (AUC) values for patients with renal impairment were ≤70% higher compared with those in subjects with normal renal function, although this increase in exposure is not expected to be clinically meaningful . A 2‐period, single‐dose crossover phase 1 study demonstrated that there is no effect of food on the pharmacokinetics of ertugliflozin in healthy volunteers and that ertugliflozin 15 mg can be administered without regard to meal consumption . The potential for ertugliflozin to be a victim or perpetrator of clinically meaningful drug interactions is low: a number of phase 1 studies have shown that there is no clinically relevant drug‐drug interaction between ertugliflozin and metformin, sitagliptin, glimepiride, simvastatin, or rifampin…”
mentioning
confidence: 99%
“…45 Indeed, a recent study has shown that ertugliflozin 15 mg and sitagliptin 100 mg FDC tablets can be administered without regard to meals. 6 Bioequivalence was demonstrated for the 4 assessed strengths of ertugliflozin/sitagliptin FDC tablet and the individual components: for both ertugliflozin and sitagliptin, the 90%CIs for the ratios (FDC/ coadministration) of geometric means for AUC inf and C max were within the acceptance criteria for bioequivalence (80% to 125%). Although caution should be taken when drawing conclusions regarding the general clinical applicability of data from single-dose studies in healthy volunteers, all treatment combinations of ertugliflozin and sitagliptin (FDC or when coadministered) were well tolerated: no serious AEs, severe AEs, or temporary or permanent discontinuations due to AEs were observed in any of the 4 single-dose studies.…”
Section: Discussionmentioning
confidence: 81%
“…Because both agents are Biopharmaceutical Classification System class 1 compounds, a clinically meaningful food effect on exposure is unlikely due to their high solubility and permeability . Indeed, a recent study has shown that ertugliflozin 15 mg and sitagliptin 100 mg FDC tablets can be administered without regard to meals …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations